2011
DOI: 10.1016/j.jsps.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antimicrobial evaluation of carbostyril derivatives of 1H-pyrazole

Abstract: A new series of 12 derivatives of 4-pyrazolyl-N-arylquinoline-2,5-dione (4a-l) were synthesized by one pot base catalyzed cyclocondensation reaction of 1-aryl-5-chloro-3-methyl-1H-pyrazole-4-carbaldehyde (1a-c), Meldrum's acid (2) and 3-arylamino-5,5-disubstitutedcyclohex-2-enone (3a-d). All the compounds were characterized by elemental analysis, FT-IR, (1)H NMR and (13)C NMR spectral data and were screened, against six bacterial pathogens, namely Bacillus subtilis, Clostridium tetani, Streptococcus pneumoniae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Owing to the various biological properties of pyrazole derivatives such as anti-cancer (Fu et al, 2010), anti-inflammatory (Bharate et al, 2008 and antimicrobial activities (Thumar & Patel, 2011), we have during the course of our medicinal chemistry research reported the synthesis and bioactivity of pyrazole derivatives (Abdel-Aziz et al, 2009, 2010AbdelWahab et al, 2009). The title compound (I) was synthesized and characterized in order to study the structure activity relationship of this class of compounds.…”
Section: Commentmentioning
confidence: 99%
“…Owing to the various biological properties of pyrazole derivatives such as anti-cancer (Fu et al, 2010), anti-inflammatory (Bharate et al, 2008 and antimicrobial activities (Thumar & Patel, 2011), we have during the course of our medicinal chemistry research reported the synthesis and bioactivity of pyrazole derivatives (Abdel-Aziz et al, 2009, 2010AbdelWahab et al, 2009). The title compound (I) was synthesized and characterized in order to study the structure activity relationship of this class of compounds.…”
Section: Commentmentioning
confidence: 99%
“…Carbostyril [2( 1H )‐quinolone] derivatives can be found among compounds of biological – antimicrobial, antitumour, antibacterial, antifungal, etc. – activity . Some of these are also used as fluorescent probes for cations and thiols .…”
Section: Introductionmentioning
confidence: 99%
“…The pyrazoles possessing a formyl group –CHO at the 4‐position are versatile organic synthetic intermediates for the synthesis of many heterocyclic ring systems such as pyrazolylpyrazolines , pyrazoloquinolinones , 4 H ‐pyrazolopyran , pyrazolylbenzoxazole , pyrazolothiadiazepines , pyrazolyloxazolone , pyrazolyloxadiazolines , pyrazolylthiadiazolines , imidazolylpyrazoles , pyrazolopyridines , chromenopyrazolones , and thiopyranothiazolylpyrazoles . These are equally important in the field of medicinal as well as pharmaceutical chemistry because of significant biological activities, such as anti‐inflammatory , antioxidant, antibacterial, and antifungal activities .…”
Section: Introductionmentioning
confidence: 99%